Phage Inactivation of Listeria monocytogenes on San Daniele Dry-Cured Ham and Elimination of Biofilms from Equipment and Working Environments - Lucilla Iacumin; Marisa Manzano; Giuseppe Comi (Microorganisms, 2016)
The anti-listerial activity of generally recognized as safe (GRAS) bacteriophage Listex P100 (phage P100) was demonstrated in broths and on the surface of slices of dry-cured ham against 5 strains or serotypes (i.e., Scott A, 1/2a, 1/2b, and 4b) of Listeria monocytogenes. In a broth model system, phage P100 at a concentration equal to or greater than 7 log PFU/mL completely inhibited 2 log CFU/cm2 or 3 log CFU/cm2 of L. monocytogenes growth at 30 °C. The temperature (4, 10, 20 °C) seemed to influence P100 activity; the best results were obtained at 4 °C. On dry-cured ham slices, a P100 concentration ranging from 5 to 8 log PFU/cm2 was required to obtain a significant reduction in L. monocytogenes. At 4, 10, and 20 °C, an inoculum of 8 log PFU/cm2 was required to completely eliminate 2 log L. monocytogenes/cm2 and to reach the absence in 25 g product according to USA food law. Conversely, it was impossible to completely eradicate L. monocytogenes with an inoculum of approximately of 3.0 and 4.0 log CFU/cm2 and with a P100 inoculum ranging from 1 to 7 log PFU/cm2. P100 remained stable on dry-cured ham slices over a 14-day storage period, with only a marginal loss of 0.2 log PFU/cm2 from an initial phage treatment of approximately 8 log PFU/cm2. Moreover, phage P100 eliminated free L. monocytogenes cells and biofilms on the machinery surfaces used for dry-cured ham production. These findings demonstrate that the GRAS bacteriophage Listex P100 at level of 8 log PFU/cm2 is listericidal and useful for reducing the L. monocytogenes concentration or eradicating the bacteria from dry-cured ham.